Mental health education on college students’ english vocabulary memorization from the perspective of STEAM education - Wang, Yu (Frontiers in Psychology, 2022)
The formation and research of Constructivism theory is another understanding in developing educational psychology. Many problems exist in English vocabulary teaching and learning, which are too common to be noticed, negatively and implicitly impacting students' English Vocabulary Memorization (EVM). In order to solve these problems, this work studies college students' EVM from the perspective of Constructivism. Firstly, the literature review and observation method understand the students' EVM performance and teaching behavior. Secondly, it analyzes the current situation, problems, and reasons for students' poor EVM abilities. Finally, combined with relevant theories, a college students' EVM-oriented teaching model is proposed, whose effectiveness is verified by teaching experiments. The experiment recruits100 freshmen, including 60 boys and 40 girls, and lasts half a semester. The average score of the final exam in the experimental group is more than 90, which is better than that in the control group. Then, the SPSS21.0 is used in the independent-samples t-test, finding no significant difference (P < 0.05). Thus, the experimental group's comprehensive English Proficiency Level (EPL) has not been negatively affected. The proposed teaching model can improve students' EVM efficiency and consolidate their memory. The proposal has important guiding significance for stimulating students' interest in English vocabulary learning and the quality of vocabulary teaching.